h.hofstede (h.hofstede@hogeland.nl)

       
1. a. u = (x- 2)
u2 = x - 2
x = u2 + 2
dx = 2udu
invullen in de integraal:
 
   
    u = (x- 2) terug invullen:

F = 2/5(x - 2)2,5 + 8/3(x- 2)1,5 + 6(x- 2)0,5
       
  b. u = (x - 1)1/3
u3 = x - 1
x = u3 + 1
dx = 3u2du
invullen in de integraal:
 
     
    u = (x - 1)1/3  terug invullen:

F = 3/5(x - 1)5/3 + 3/2(x- 1)2/3
 
       
  c. u = x
x = u2
dx = 2udu
invullen in de integraal:
 
     
    u = x  terug invullen:

F = 2lnx+ 1
 
       
  d. u = (x+ 1)1/5
u5 =  x +  1
x = u5 - 1
dx = 5u4du
invullen in de integraal: 
 
   
    u = (x+ 1)1/5  terug invullen:

F = 5/9(x+ 1)9/5 - 5/4(x + 1)4/5
 
       

h.hofstede (h.hofstede@hogeland.nl)